Managing human resources - George Bohlander (Thomson, 2007)
The #1 textbook on the market, MANAGING HUMAN RESOURCES covers all aspects of human resource management and its impact on both individuals and organizations. The text builds on a foundation of research and theory but also provides a practical framework focusing on critical issues and successful practices. Users and reviewers of the text praise its pleasant writing style, user-friendly design, and highly effective examples that provide meaningful insight into the world of HR. In fact, over 500 different organizations from a variety of settings are used as examples to illustrate key points and make the connection to HR practice. Important issues and critical trends are spotlighted in each chapter and reflected in the comprehensive and chapter ending cases included in the text. Managing Human Resources' balance of theory and practice, hands-on activities, applications, and examples helps students develop the competencies to understand and help their organizations create a sustainable competitive advantage through people